Kinetic study of catalytic glycolysis of PET wastes with zinc acetate - Tatt, Chan Wei (2013)
Poly(ethylene terephthalate) (PET) was depolymerized by di-ethylene glycol (DEG) in the presence of zinc acetate. Qualitative analysis showed that the main product from glycolysis was bis(hydroxylethyl) terephthalate. Fourier Transform infra-red (FTIR) was used for characterization of product while thermo-gravimetry analysis (TGA) and differential scanning calorimetry (DSC) were used for thermal analysis. The respond surface methodology (RSM) was used to predict the optimum conditions of reaction which includes time, temperature, amount of catalyst and amount of DEG. Besides that, the analysis of variance (ANOVA) was employed to evaluate the validity of the developed model. The maximum conversion obtained from RSM was 99.79%, The optimum temperature, time, amount of catalyst and amount of DEG were 183.37 °C, 0.82 hour, 0.09 g and 10.33 g respectively. Lastly, a simple theoretical power-law model was developed to predict the time evolution of conversion. This kinetic model was found to be consistent with the experimental data. From the study, activation energy and enthalpy of reaction of 38.24 kJ/mol and 14.87kJ/mol were obtained, respectively.